A Study on the Association between Poverty, Demographics, Family Support, and Cancer Care in Jharkhand, India - Imteyaz Ahmad; Padmaja Gadiraju; Punam Singh; Ranjit Kumar Dehury; C. Vanlalhruaii; MD Tabrez Alam; Parthsarathi Dehury (ACHSM, 2024)
Objective: The complex relationship between cancer care and poverty was examined in this study. This study identified the associations of various demographic factors with cancer care. The study also analyzes the family's role and support network in cancer care. Methodology: This study employed a mixed-method approach to understand cancer care in Jharkhand, India, comprehensively. The study was conducted as a cross-sectional survey with 204 reproductive cancer patients. The structured interview schedule covered the socio-demographic variables and cancer care facilities. The study also used case study methods with three eligible adults who underwent or are currently receiving cancer treatment. Descriptive statistics were used to summarize the study findings. The narratives of each case study provide a comprehensive understanding of each patient's journey to cancer care. The study received ethical approval from the Institutional Review Board (IRB) and the Cancer Hospital. Results: The survey results show that 47 percent of the respondents access the treatment. Only 12.7 percent of the respondents had taken the HPV vaccine, and 44.6 percent had received physiotherapy during the treatment. Forty-four percent of the respondents accessed counseling services from health service providers. The respondents' characteristics, such as age and gender, were strongly associated with access to counseling services. Education and family income were statistically associated with access to cancer care treatment. Only 7.4 percent of respondents arranged transport for treatment, and 11.8 percent arranged logistics and various treatment therapies for cancer care. Cancer patients from Jharkhand frequently face discrimination in receiving health care because of their economic condition. The case study revealed differences in wealth, social class and family role in cancer care. As a result, cancer patients often feel hopeless and isolated, leading to depression and anxiety. Conclusion and Implications: Poverty plays a negative role in providing and accessing cancer care in the state of Jharkhand. The role of family and society is essential for cancer survival. Psychological support from the family gives hope to the life of cancer patients. To address the complex relationship between financial burden and cancer care, both government agencies and social structures must implement comprehensive strategies.